Auto‐Oxidative Coupling of Glycine Derivatives1. Issue 49 (6th October 2014) - Huo, Congde; Yuan, Yong; Wu, Mingxia; Jia, Xiaodong; Wang, Xicun; Chen, Fengjuan; Tang, Jing
Abstract The unprecedented title reaction between glycine derivatives and indoles, as well as the auto‐oxidative Povarov/aromatization tandem reaction of glycine derivatives with olefins are described. The reactions were performed in the absence of redox‐active catalysts and chemical oxidants under mild reaction conditions. Only simple organic solvents and air (or O2) were required.